Exam ref 70-412 : configuring advanced Windows Server 2012 services - Mackin, J. C. (Microsoft Press, 2014)
Fully updated for Windows Server 2012 R2, and designed for experienced IT professionals ready to advance their status, this Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the MCSA or MCSE level.